Aligning Transition Dipole Moment toward Light Amplification and Polarized Emission in Hybrid Perovskites. Issue 20 (9th July 2021) - Qin, Jiajun; Zhang, Jia; Shen, Tangyao; Wang, Heyong; Hu, Bin; Gao, Feng
Abstract: Orientational manipulation of transition dipole moment (TDM) plays an important role in controlling the polarization of excited states in light emission as well as lasing actions. The present work discovers vertically aligned TDMs in hybrid perovskite films through angle‐resolved photoluminescence (PL) measurements, which show enhanced emission through the film edge. With increasing excitation intensity, the edge emission induced by these vertically aligned TDMs becomes dominant and eventually leads to amplified spontaneous emission (ASE) through the edge view. Meanwhile, polarized emission of both PL and electroluminescence (EL) provides further evidence for vertically aligned TDMs. Surprisingly, the degree of polarization (DOP) through the film edge is increased when grain boundary defects are passivated through either stochiometric engineering or self‐passivation by mobile ions under working conditions. With increasing DOP, ASE threshold of the perovskite film is reduced owing to enhanced collective behaviors of light‐emitting states. This work presents a useful method to manipulate TDMs in organic–inorganic hybrid perovskites. Abstract : Vertical aligned transition dipoles are demonstrated in methylammonium lead bromide, leading to linearly polarized photoluminescence and electroluminescence (EL). The emission with polarization direction perpendicular to the film plane indicates coherent interaction between excited states and is responsible for the light amplification. Through defect passivation, the degree of polarization of EL increases and amplified spontaneous emission threshold reduces.